multiflexxlib: A Python package for data reduction and visualization for the cold-neutron multi energy wide angle analyzer MultiFLEXX - Siqin Meng; Rasmus Toft-Petersen; Lijie Hao; Klaus Habicht (SoftwareX, 2018)
A Python software package for data reduction and visualization of continuous angle multiple energy analysis (CAMEA) type detector backend MultiFLEXX is presented. The software concept focuses on unambiguous, automated aggregation of experimental data and preservation of raw data structure in graphical representation, enabling on-the-fly analysis of experimental data from MultiFLEXX with minimal amount of user input, reducing confusion and human error in studies involving multiple parameters. The software also provides a set of interfaces for versatile tweaking of graphing parameters, facilitating generation of production-quality graphs for use in publications. The software enhances the role of MultiFLEXX as a swift mapping option available at the cold-neutron triple-axis spectrometer FLEXX. Keywords: Inelastic neutron scattering, Three-axis spectroscopy, Visualization tool